Tear soup a recipe for healing after loss - Schwiebert, Pat.; DeKlyen, Chuck; Bills, Taylor; McDonald-Lewis, Mary.; Grief Watch (Portland, Or. : Grief Watch, 2006)
Tear Soup, a recipe for healing after loss, centers around an old and somewhat wise woman, Grandy. Grandy has just suffered a big loss in her life and so she is headed to the kitchen to make a special batch of Tear Soup. There she chooses the size pot that is right for her loss, and she puts on her apron because she knows it's going to be messy. Slowly the pot is filled with tears as the old woman steeps away. To season her soup Grandy adds memories like the good times and the bad times, the silly and the sad times. She does not want to forget even one precious memory of her loss.
DVD.
Produced by Pat Schwiebert; directed by Paul Ramsey.
Narrated by Mary McDonald-Lewis.
Companion DVD to the book: Tear soup.
Keywords: Loss (Psychology) -- Juvenile films; Grief -- Psychological aspects -- Juvenile films; Bereavement -- Psychological aspects -- Juvenile films; Separation (Psychology) -- Juvenile films